Development of instrument critical and creative thinking skills on fluids motion - S N Utami; P Siahaan; A Setiawan (Pascasarjana Universitas Pendidikan Indonesia, 2018)
21st century skills focus on critical thinking skills, creative thinking skills, communication skills and collaboration skills. The student critical and creative thinking skills are defined as the ability of student use their knowledge to solve problems of everyday life and create a new innovation. The main goal of this study developed to measured critical and creative thinking skills for student in senior high school. The instrument has 34 items consist of 18 items critical thinking skills and 16 items creative thinking skills. All instrument have been validated by three expert judgement. So, the instrument obtained 17 items consist of nine items critical thinking skills and eight items creative thinking skills. This research use descriptive qualitative research method. The results development instrument test show all items are valid through the Pearson moment correlation coefficient test. Based on expert assessment and data collection, instruments were well developed and could be used to measure students' critical and creative thinking skills on the concept of fluids motion.